Recent developments in configuration design and optimization of mineral separation circuits; A Review - vahid radmehr; Ziaedine Shafaei; Mohammad Noaparast; Hadi Abdollahi (International Journal of Mining and Geo-Engineering, 2019)
The present research reviews two basic approaches for the separation circuit configuration analysis. The first approach is to optimize the circuit configuration. In this method, after a circuit modeling, a variety of search algorithms and mathematical optimization methods are used. Previous works show that this approach has more application in the flotation process. The second approach called the circuit analysis, evaluates the circuit configuration by considering a transfer function for each separation unit. This method provides great freedom for conducting a variety of investigations on the separation circuits.